2003
DOI: 10.1101/gad.1103603
|View full text |Cite
|
Sign up to set email alerts
|

Integral role of Noxa in p53-mediated apoptotic response

Abstract: The tumor suppressor p53 exerts its versatile function to maintain the genomic integrity of a cell, and the life of cancerous cells with DNA damage is often terminated by induction of apoptosis. We studied the role of Noxa, one of the transcriptional targets of p53 that encodes a proapoptotic protein of the Bcl-2 family, by the gene-targeting approach. Mouse embryonic fibroblasts deficient in Noxa [Noxa −/− mouse embryonic fibroblasts (MEFs)] showed notable resistance to oncogene-dependent apoptosis in respons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
266
0
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 308 publications
(278 citation statements)
references
References 25 publications
9
266
0
3
Order By: Relevance
“…For example, Noxa and Puma are transcriptionally regulated by p53 and have been implicated in fibroblast anoikis [27,28]. Furthermore, in epithelial cells the Bcl-2 modifying factor (Bmf) behaves as sentinel able to register damage at the cytoskeleton and to convey a death signal.…”
Section: Intrinsic Pathwaymentioning
confidence: 99%
“…For example, Noxa and Puma are transcriptionally regulated by p53 and have been implicated in fibroblast anoikis [27,28]. Furthermore, in epithelial cells the Bcl-2 modifying factor (Bmf) behaves as sentinel able to register damage at the cytoskeleton and to convey a death signal.…”
Section: Intrinsic Pathwaymentioning
confidence: 99%
“…EGL-1 induction plays a predominant role in DNA damage-induced apoptosis, while CED-13 appears to be important for UV-induced apoptosis (Schumacher et al 2005a ;Stergiou et al 2007 ) . Conceptually, the worm CEP-1 pathway acts analogously to the mammalian p53-dependent apoptosis induction of the BH3 proteins Puma and Noxa, which in turn leads to apoptosis induction analogous to EGL-1 by Bcl-2/CED-9 inactivation (Jeffers et al 2003 ;Villunger et al 2003 ;Shibue et al 2003 ;Oda et al 2000 ) . The cep-1 null mutant worms do not have any overt developmental or germline-speci fi c phenotype but are fully defective in DNA damage-induced apoptosis.…”
Section: Pathways Leading To Dna Damage-induced Apoptosismentioning
confidence: 99%
“…68 Studies have demonstrated that MEFs lacking PUMA or Noxa are resistant to DNA damage-induced apoptosis, a process known to be mediated by p53. [69][70][71] Another class of proapoptotic genes that can be regulated by p53, such as Fas or DR5/KILLER, are components of the apoptotic extrinsic pathway. 72 Finally, genes that encode redox-regulating enzymes such as the PIGs (p53-induced genes), which are involved in reactive oxygen species production, can damage the mitochondria, leading to apoptosis.…”
Section: Proapoptotic Bidmentioning
confidence: 99%